Komunikasi Terapetik pada Pasien Pasca Operasi dalam Penerapan Pasien Safety Terhadap Pelayanan Keperawatan - Sulistiorini Kurniawati; Ida Faridah (Malahayati Nursing Journal, 2023)
ABSTRACT Therapeutic communication is communication that has a specific purpose, namely to achieve the goal of healing. The implementation of therapeutic communication is carried out on all patients, one of which is postoperative patients. This study aims to determine the effect of therapeutic communication on postoperative patients in the implementation of patient safety (fall risk) on nursing services at Hermina Bitung Hospital. This research is a quasi-experimental study with a research design of One group Pre-Post test Design. The sampling technique in this study was simple random sampling with a sample size of 88 people. The data analysis carried out is univariate and bivariate analysis. The statistical test used is the Wilcoxon test. From the results of the study, the average value of therapeutic communication before the intervention was 59.95 and after the intervention was 66.24. The average value of nursing services before the intervention was 39.56 and after the intervention was 43.86. From the results of the Wilcoxon test, a significant value of 0.000, means that there is an influence of the influence of therapeutic communication on postoperative patients in the implementation of patient safety (risk of falling) on nursing services. From the results of the study, it can be concluded that there is an effect of therapeutic communication on postoperative patients in the implementation of patient safety (risk of falling) on nursing services. Keywords: Therapeutic Communication, Nursing Services, Patient Safety  ABSTRAK Komunikasi terapetik merupakan komunikasi yang memiliki tujuan yang spesifik yaitu untuk mencapai tujuan kesembuhan. Pelaksanaan komunikasi terapetik dilakukan pada semua pasien, salah satunya kepada pasien pasca operasi. Penelitian ini bertujuan untuk mengetahui pengaruh komunikasi terapetik pada pasien pasca operasi dalam pelaksanaan pasien safety (resiko jatuh) terhadap pelayanan keperawatan RS Hermina Bitung. Penelitian ini merupakan penelitian quasi eksperimen dengan desain penelitian One group Pre-Post test Design. Tekhnik sampel dalam penelitian ini adalah simple random sampling dengan jumlah sampel 88 orang. Analisa data yang dilakukan adalah analisa univariat dan bivariat. Uji statistik yang digunakan adalah uji Wilcoxon.  Dari hasil penelitian diperoleh nilai rata – rata komunikasi terapetik sebelum intervensi adalah 59,95 dan setelah intervensi adalah 66,24. Nilai rata – rata pelayanan keperawatan sebelum intervensi adalah 39,56 dan setelah intervensi adalah 43,86. Dari hasil uji Wilcoxon diperoleh nilai sginifikan 0,000, artinya terdapat pengaruh pengaruh komunikasi terapetik pada pasien pasca operasi dalam pelaksanaan pasien safety (resiko jatuh) terhadap pelayanan keperawatan. Dari hasil penelitian dapat disimpulkan terdapat pengaruh pengaruh komunikasi terapetik pada pasien pasca operasi dalam pelaksanaan pasien safety (resiko jatuh) terhadap pelayanan keperawatan. Kata Kunci: Komunikasi terapetik, Pelayanan Keperawatan, Pasien Safety